2018
DOI: 10.1016/j.compositesb.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Simple and effective models to predict the compressive and tensile strength of HPFRC as the steel fiber content and type changes

Abstract: HPFRC/UHPC are today widely applied as repair and reinforcement materials for structures. One of the\ud drawback of commercial HPFRC/UHPC is that any modification of the matrix-fibers mix design, due to the\ud market requirements, affects the mechanical properties of the hardened concrete and therefore the data obtained\ud testing the previous version of the concrete are useless. Prediction models that link the properties of bothfibers\ud and matrix to the performances of the hardened concrete are of great pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 34 publications
(30 reference statements)
1
38
0
Order By: Relevance
“…e test results also showed that the splitting tensile strength increases with the increase in fiber content, which is frequent in the literature [41][42][43][44]. e increase in splitting tensile strength can easily be attributed to the fiber bridging potential of tensile cracks.…”
Section: Results Of Control Testsmentioning
confidence: 56%
“…e test results also showed that the splitting tensile strength increases with the increase in fiber content, which is frequent in the literature [41][42][43][44]. e increase in splitting tensile strength can easily be attributed to the fiber bridging potential of tensile cracks.…”
Section: Results Of Control Testsmentioning
confidence: 56%
“…The repairing consisted in the restoration of the damaged portion of the longitudinal steel reinforcement by means of turned rebar parts and substitution of the stirrups and the damaged concrete parts with HPFRC (High Performance Fiber Reinforced Concrete). A detailed description of the repairing process can be found in (Albanesi, Lavorato, Nuti, & Santini, 2009;Lavorato, Nuti, Santini, Briseghella, & Xue, 2015;Savino, Lanzoni, Tarantino, & Viviani, 2018). The cyclic test, which was carried out firstly on the pier P16-1B and consequently on the pier R16-1B, consisted in the imposition of a displacement history at the top of the pier.…”
Section: Experimental Testmentioning
confidence: 99%
“…[33,39,45]. The work of [35] focused both to predict the tensile strength by uniaxial tests, being more realistic than splitting tests, and to improve the reliability of previous models extending the investigation towards more types of fibers and dosages. Despite the good results, its application was limited to the fact that only one type of matrix was investigated, confirming its reliability only for concretes with the same strength range (HPFRC).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the good results, its application was limited to the fact that only one type of matrix was investigated, confirming its reliability only for concretes with the same strength range (HPFRC). The present work aims at extending the model proposed in [35] in order to predict the compressive and the uniaxial tensile strengths for any HPFRC/UHPFRC as matrix and fiber properties change.…”
Section: Introductionmentioning
confidence: 99%